2016
DOI: 10.1371/journal.pone.0168103
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Lifetime Domestic Violence: Associations with Mental Health and Stress among Pregnant Women in Rural Bangladesh: The MINIMat Randomized Trial

Abstract: BackgroundExperience of domestic violence has negative mental health consequences for women. The association of cumulative and specific forms of domestic violence, particularly emotional violence and controlling behavior, with common mental disorders and stress has rarely been studied in pregnant women. The aim of this study is to evaluate associations of specific and multiple forms of lifetime domestic violence and controlling behavior with distress and cortisol level during pregnancy in rural Bangladeshi wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
7
25
0
2
Order By: Relevance
“…As mentioned above, Iranian women with IPV experiences do not have considerable social and family support due to cultural and traditional issues. Thus, this result is comparable to previous findings in this field (Hosseini, Beyrami & Hashemi 2012;Ziaei et al 2016;Wiess et al 2017). Results of Hosseini study among families of supervisor women indicate that emotional-focused coping styles (escape-avoidance, meeting and seeking social support) and social support variables can predict significantly vulnerability against stress (Hosseini, Beyrami & Hashemi 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As mentioned above, Iranian women with IPV experiences do not have considerable social and family support due to cultural and traditional issues. Thus, this result is comparable to previous findings in this field (Hosseini, Beyrami & Hashemi 2012;Ziaei et al 2016;Wiess et al 2017). Results of Hosseini study among families of supervisor women indicate that emotional-focused coping styles (escape-avoidance, meeting and seeking social support) and social support variables can predict significantly vulnerability against stress (Hosseini, Beyrami & Hashemi 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reveal that women with IPV experiences are more likely to report physical and emotional symptom of stress (Ziaei et al 2016;Wiess et al 2017). The results of Weiss et al (2017) study among women experiencing partner violence demonstrate that greater avoidance coping is related to more symptoms of PTSD in American women.…”
Section: Discussionmentioning
confidence: 99%
“…Intimate partner violence (IPV) is the one of the most important risk factors found in our study, which was consistent with most of the literature of postpartum depression [2, 13, 4550]. In a recent study of Bangladesh, Ziaie found that all forms of domestic violence were strongly associated with higher levels of emotional distress during the pregnancy period as well [51]. In our study, we also found that poor marital relationship (sharing personal feelings and practical support in household work) with husbands was a strong predictor of PPD, consistent with the findings of other studies [1, 52].…”
Section: Discussionsupporting
confidence: 91%
“…They also reported that 20–75% of women experienced at least one psychologically abusive act by their partner in their lifetimes. High rates of lifetime physical (42–51%), sexual (37–50%), and psychological (28%) IPV against women in Bangladesh have been documented in several population‐based studies (Garcia‐Moreno et al, ; Koenig, Ahmed, & Hossain, ; Ziaei, Frith, Ekström, & Naved, ). However, these figures depend on the definitions, assessment tools, and population used.…”
Section: Introductionmentioning
confidence: 99%